The Influence of Control on Belief in Conspiracy Theories: Conceptual and Applied Extensions - van Prooijen, Jan-Willem; Acker, Michele (Applied cognitive psychology, 2015)
Summary Threats to control have been found to increase belief in conspiracy theories. We argue, however, that previous research observing this effect was limited in two ways. First, previous research did not exclude the possibility that affirming control might reduce conspiracy beliefs. Second, because of artificial lab procedures, previous findings provide little information about the external validity of the control threat–conspiracy belief relationship. In Study 1, we address the first limitation and find that affirming control indeed reduces belief in conspiracy theories as compared with a neutral baseline condition. In Study 2, we address the second limitation of the literature. In a large‐scale US sample, we find that a societal threat to control, that citizens actually experienced, predicts belief in a range of common conspiracy theories. Taken together, these findings increase insight in the fundamental relationship between the human need for control and the tendency to believe in conspiracy theories. Copyright © 2015 John Wiley & Sons, Ltd.